Internal Control System Analysis of Cash Receiving at Adeeva Hotel, Bengkulu City - Neli Puspita Sari; Sulisti Apriani; Herlin Herlin (Journal of Indonesian Management, 2021)
The purpose of this study is to determine the internal control system for cash receipts at Hotel Adeeva Bengkulu City, especially cash receipts from cash sales. Data collection tools were carried out by means of documentation and unstructured interviews. The analytical method used is comparative analysis comparing the theory put forward by Mulyadi Hotel Adeeva Bengkulu City regarding the cash receipt internal control system. The results of this study indicate that the internal control analysis of cash receipts at the Adeeva Hotel, Bengkulu City, is not good enough because there is still no separation of functions and there is an overlap between the existing functions of the front office. The authorization system and recording procedures at the Adeeva Hotel in Bengkulu City are inadequate, because there is a one-way system where the front office still has dual duties as seen from the reception of guests and supervises payments at the cashier. Employ competent Adeeva Hotel, Bengkulu City, has conducted training for new employees and conducted a fairly strict employee selection before being accepted as employees